O impacto de reestruturação e privatização na gestão integrada do setor de energia elétrica: análise do setor a partir da abordagem de redes - Peci, Alketa (2000)
The Brazilian energetic sector is passing through deep transformations. The restructure is mainly characterized by the passage from a vertical and centrally coordinated system, in hands of the State, to a more horizontal one, with characteristics of a network, in which organizations, such as the National Agency of Electric Energy (ANEEL), the new regulator entity, the Wholesaler Market of Electric Energy (MAE), the National Operator of Electric System (ONS), Eletrobrás and the National Bank of Economic and Social Development (BNDES) are designated as the principals integrators of the system. The objective of the present work was to analyze the influence of the privatization and restructuring processes in the integration of the Brazilian system of electric energy. The analysis was based on the instruments offered by the network approach. The results of the research show that the Brazilian sector of electric energy cannot be considered as a highly integrated network. In this new horizontal configuration, the social actors are affirming its roles, functions and objectives, while the key-organization like ANEEL, ONS, MAE, Eletrobrás, and BNDES are being structured to strengthen its integrative role.